PENGEMBANGAN LEMBAR KERJA SISWA (LKS) QR CODE MENGGUNAKAN KONTEKS KOTA LUBUKLINGGAU PADA MATERI BANGUN DATAR SEGIEMPAT KELAS VII SMP NEGERI 3 LUBUKLINGGAU - Leni Lestari Aprilia; Maria Luthfiana; Rani Refianti (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to produce a QR Code Student Worksheet (LKS) using a valid and practical Lubuklinggau City context, as well as potential effects. This research is a development research using a 4D model. This model is carried out by researchers consisting of 4 stages, namely: define (defining stage), design (planning stage), develop (development stage) and disseminate (dissemination stage). Data was collected using questionnaires, interviews, and tests. The subjects of this study were students of class VII.9 with a total of 32 students. From the results of the study obtained a valid learning media with a validity of 3.24 and practical with a practicality result of 96.22%; and has a potential effect on student learning outcomes where 29 students (90.62%) are included in the category of having completed, while there are 3 students (9.37%) who have not completed the Minimum Learning Completeness (KBM) determined by the school, the minimum student gets a score of 65 The potential effect of learning media is categorized as very good.